You are on page 1of 1

Problem Corner | Solution 279 | by Benjamin Bloch, Ph.D.

1.  Since the derivative of sin x equals cos x, and the derivative of cos x equals -sin x, taking the derivative of each and substituting we get: y’ = - sin2 x + cos2 x 2.  Substituting gives us: y’ = (sin x)(cos x) + (sin x)(cos x) = 2(sin x)(cos x)  From Problem 273 we see that this equation is also of the form y = f(x)n, where y’ = nf(x)n-1f’(x), where f(x) = sinx, and n = 2, so that immediately y’ = 2(sinx)(cosx) 3. y’ = xcos x + sin x 4.  Rewriting the equation as y = (xcos x + 1)/x2 = (xcos x + 1)x-2 we get y’ = -2x-3 (xcos x + 1) + x-2(-xsin x + cos x) = -2x-2cos x -2x-3 - x-1sin x + x-2cos x = -x-1sin x - x-2cos x - 2x-3 = -x-1(sin x + x-1cos x + 2x-2)